Seychelles : Central Bank Transparency Code Review. (IMF Staff Country Reports; Country Report, 2022)
The Central Bank of Seychelles (CBS) sets a high benchmark for transparency, given the economic, and financial development and literacy circumstances of Seychelles, which is recognized by the stakeholders, thus maintaining a high level of trust and accountability. Despite constrained human capital resources, the CBS has taken commendable actions to facilitate an open and dynamic dialogue with key stakeholders. The CBS took the lead in communications on extraordinary support programs during the COVID-19 pandemic, regularly engaging with the public using plain language and various communication tools. It is also making great efforts to promote financial inclusion in Seychelles by developing and implementing a broad agenda on financial education and enhancing consumer protection in the financial sector.